Reduced Mortality Associated With the Use of Metformin Among Patients With Autoimmune Diseases - Lin, Chun-Yu; Wu, Chun-Hsin; Hsu, Chung-Yuan; Chen, Tien-Hsing; Lin, Ming-Shyan; Lin, Yu-Sheng; Su, Yu-Jih (Frontiers in Endocrinology, 2021)
Objective: Metformin has been linked to anti-proliferative and anti-inflammatory mechanisms. In this study, we aimed to examine the long-term impact of metformin on mortality and organ damage in patients with autoimmune diseases and type 2 diabetes mellitus (T2DM). Methods: We conducted a cohort study using the National Health Insurance Research Database in Taiwan between 1997 and 2013. Based on metformin and other anti-diabetic agent prescriptions, we categorized all patients with autoimmune diseases into either the metformin group (metformin administration for at least 28 days) or the non-metformin group. The primary outcomes were all-cause mortality and annual admission rate, while the secondary outcome was target organ damage. We followed patients from the index date to the date on which the event of interest occurred, death, or the end of this study. Results: Our cohort study included 3,359 subjects for analysis. During a mean follow up of 5.2 ± 3.8 years, the event rate of all-cause mortality was 228 (33.6%) in the metformin group and 125 (36.9%) in the non-metformin group. The risk of both all-cause mortality and annual number of admissions for autoimmune diseases was significantly lower in the metformin group than in the non-metformin group [hazard ratio (HR) 0.77; 95% CI 0.62–0.96 and risk ratio (RR) 0.81; 95% CI 0.73–0.90, respectively]. Conclusion: Metformin may add benefits beyond T2DM control with regard to reducing all-cause mortality and admission rate, as well as minimizing end-organ injury in lungs and kidneys among patients with autoimmune diseases.